Analysis of the Construction of China’s Grain Supply Chain System in 2023 - HONG Tao (Liang you shipin ke-ji)
The paper analyzed the current state of China's grain supply chain in 2023, highlighting the continuous innovations in various aspects, including production, import and export, storage, transportation, processing, and sales. It summarized the exploration of various supply chain models in practice, such as the futures market, group enterprises, wholesale markets (National Grain Trade Centers), logistics companies, new retail enterprises, digital technology companies, production bases, fertilizer companies, exhibitions, "grain logistics channels," provincial regional brands, and the grain logistics supply chain, etc. The paper analyzed the existing problems in China's grain supply chain innovation and application, and identified seven major trends in the development of the grain supply chain, namely digitalization, greening, safety, globalization, coordination, intelligence, and standardization. It also put forward policy recommendations for China's grain supply chain innovation.